Loss of Recurrent Laryngeal Papillomatosis following Postsurgical Treatment with dsRNA Interferon Inducer - Alina Sultanova; Liba Sokolovska; Maksims Cistjakovs; Andrejs Lifsics (Case Reports in Infectious Diseases)
Laryngeal papillomatosis (LP) is the most common benign laryngeal tumor in children, but it can affect both children and adults. Although benign, this condition still remains hard to treat and negatively affects patient quality of life as it can spread to the adjacent respiratory tract, recurs, and requires repeated medical intervention. As the surgical removal of papillomas with the preservation of normal mucosa is the only standard of care, there is still no standard for adjuvant therapy. In this case report, we describe the course of recurrent laryngeal papillomatosis in a Caucasian male from 2009 to 2016 and the positive response to dsRNA-based antiviral drug treatment in the complete resolvement of the condition.